Create a Security Control System to Prevent Hackers from Tampering with IoT Devices - Ahmed , Saja Talib; Abdullah , Dhahir Abdulhade (Journal of Ecohumanism, 2024)
With the expansion of the use of Internet of Things using Internet technology to control and operate highly confidential systems in areas of life and with government facilities such as hospitals or banks, they require high security for their system in both software and hardware to prevent theft by unauthorized persons, and only authorized persons can enter the system. Our proposed work includes an authentication system to enter the Internet of Things system. Where SoC is used to generate True Random Numbers. These numbers are used to reconnect the pins of the devices. Where the encryption of the random code is changed every time an attempt is made to enter the system by unauthorized persons by entering the password and username incorrectly, using SoC (4 Cortex-M chip) by generating a new code instead of changing the connection of the logical controllers. The random numbers are unpredictable, unique and cannot be predicted. TRNs were tested using NIST tests, and they achieved high results. The test results of these numbers also showed that they are unpredictable, unique, have a high entropy value per bit (0.999) and have no correlation with the value (-0.12333). Which means that reconnecting the pins to operate the devices is a difficult process to predict because it depends on numbers generated physically, not mathematically, and cannot be predicted.